Towards a linguistic description of dependencies in data - Batyrshin, Ildar; Wagenknecht, Michael (Zielona Góra: Uniwersytet Zielonogórski)
The properties of the genetic algorithm used for construction of the optimal partition and several methods of data re-translation are described. The methods are illustrated by examples, and potential applications of the proposed methods are discussed.
Keywords: fuzzy approximation; linguistic term; fuzzy rule; genetic algorithms